Determination of Platycodin D and Platycodin D3 in Rat Plasma Using Liquid Chromatography-Tandem Mass Spectrometry - Tae-Hyun Kim; Byung Eui Lee; Eun Joo Kim; Yong Seok Choi; Keun-Sung Lee; Hak Rim Kim; Hyung-Gun Kim (The Scientific World Journal)
Platycodon grandiflorum has long been used as a traditional oriental medicine for respiratory disorder. Platycodin D (PD) is known as the main component isolated from the root of PG. A simple and rapid liquid chromatography-tandem mass spectrometry (LC-MS/MS) method has been developed and validated for the quantitation of PD in rat plasma. Quantitation was performed on a triple quadrupole mass spectrometer employing electrospray ionization and multiple reaction monitoring in positive ion mode. The total chromatographic run time was 4.0 min, and the calibration curves of PD were linear over the concentration range of 50–10,000 ng/mL in rat plasma. The coefficient of variation and relative error at five QC levels were 1.0 to 8.8% and 0.7 to 8.7%, respectively. After a single oral administration of 500 mg/kg and a single intravenous administration of 25 mg/kg of 3% PD extract (a PG extract including 3% of PD), platycodin D and platycodin D3 were detected and pharmacokinetic parameters were estimated. The oral bioavailability of platycodin D and platycodin D3 was 0.29% and 1.35% in rats at 500 mg/kg of 3% PD extract of PG, respectively. The present method can be applied to pharmacokinetic analysis of platycodins and platycosides of the PG.